Kajian Etnobotani dan Reproduksi Tumbuhan Obat Di Desa Jagalan Kecamatan Kwanyar Kabupaten Bangkalan - Riadul Jannah; Ari Hayati; Tintrim Rahayu (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2022)
Ethnobotany is a botanical science that studies the use of plants in the needs of daily life and tribal customs. The use of plants as traditional medicine (herbal) has been known for a long time by the people in Desa Jagalan. This study aims to identify medicinal plants, utilization of medicinal plants, and reproduction of medicinal plants by the people of Jagalan Village, Kwanyar District, Bangkalan Regency. This research was conducted in May-2019 using qualitative methods. Qualitative methods are used to collect data through interviews. Respondents were selected using purposive sampling, namely community members who knew about medicinal plants, especially for parents with an age range (35-80 years). Research shows the average data of respondents encountered 150 respondents. There are 14 types of medicinal plants used in Jagalan Village, namely Bingbuluh (Belimbing wuluh), jeih (ginger). Kencur (kencor), Sere (Sirih), Molabek Temulawak), Moereng (Temuireng), Binahong, Meronggih (Kelor), Konyek (turmeric), Mores (Soursop), Jembuh (Guava), Orange Porot (Lime), Kodduk (Noni), Blimbing (Starfruit). Reproduction is divided into two parts, namely asexual and sexual, bingbuluh, merongguh, gembuh, orange porous, mores, codduk, and blimbing including the generative and vegetatf reproduction, jihor, kencor, molabek, moereng, binahong, and konyek including rhizoma reproduction (rhizome, live root) is a stem that grows horizontally in the soil resembling roots and then in sere including artificial vegetative reproduction by grafting and ducking.